Aspects of Legal Protection in the Agreement of Selling and Purchase of Heritage Land - Adi Sanjaya; Sriono Sriono; Elviana Sagala (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims to identify and analyze the sale and purchase of land originating from inheritance and to analyze forms of legal protection for buyers in the event of problems in the process of buying and selling inherited land. The method used in this research is using the normative juridical method by taking primary data from the applicable laws and regulations, especially in Indonesia. The results of the study show that legal protection for buyers of inherited land is contained in Article 1492 of the Civil Code which provides an explanation that although at the time of the sale there is no promise of guarantee, the seller, by law, is obliged to bear the buyer against claims of rights through law to surrender all or part of the goods. sold to a third party